Assessing the spatial distribution of creativity indicators in the residential system of Hormozgan province - Keramatilah Ziyari; Ahmad Hatami (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2021)
. In the realization of the creative city in Hormozgan province are known and the indicators of the number of printing houses, the number of libraries and the number of cultural and artistic exhibitions with an impact weight of 0.0195 are known as the least effective indicators in the realization of the creative city. In line with the second goal, TOPSIS model was used and its results showed that Bandar Abbas with the value of Ci 1 has the highest level of creativity and in the port of Lengeh with the value of 0.815649 in the second place, Minab with the value of 124715 / 0 in the third rank, Qeshm with the value of 0.09292 in the fourth rank, Rudan with the value of 0.070436 in the fifth rank, Bastak with the value of 0.070352 in the sixth rank, Parsian with the value of 0.0586565 in the seventh rank, Hajiabad with the value of / 058778 0 in the eighth place, Jask with the value of 0.051672 in the ninth place, Khamir with the value of 0.04316 in the tenth place, Sirik with the value of 0.016682 in the eleventh place, Abu Musa with the value of 0.012988 in the twelfth place and Bashagard with the value of 0.008452 It is ranked last.